2021
DOI: 10.1177/21526567211056239
|View full text |Cite
|
Sign up to set email alerts
|

Successful Anti-SARS-CoV-2 Spike Protein Antibody Response to Vaccination in MAGT1 Deficiency

Abstract: Background Novel messenger RNA vaccines against severe acute respiratory syndrome coronavirus (SARS-CoV-2) have been vital in resolving the coronavirus disease-2019 (COVID-19) pandemic. Detection of neutralizing antibodies (NAbs) against the SARS-CoV-2 spike protein (S) confirms immunogenicity with high sensitivity and specificity. Few recent studies with primary and secondary immunodeficient cohorts present adequate or reduced antibody response. We describe the first reported successful response to anti-SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Besides CVID, data on the immunogenicity of the SARS-CoV-2 vaccine in patients with IEI are few and often limited to anecdotal cases or heterogeneous cohorts. Table 2 summarizes the available literature ( 19 21 , 23 , 89 , 120 , 121 , 124 , 128 ). Except for patients with XLA and combined immunodeficiency, most patients with IEI can produce anti-Spike antibodies following two vaccine doses.…”
Section: Anti-sars-cov-2 Vaccination In Inborn Errors Of Immunitymentioning
confidence: 99%
“…Besides CVID, data on the immunogenicity of the SARS-CoV-2 vaccine in patients with IEI are few and often limited to anecdotal cases or heterogeneous cohorts. Table 2 summarizes the available literature ( 19 21 , 23 , 89 , 120 , 121 , 124 , 128 ). Except for patients with XLA and combined immunodeficiency, most patients with IEI can produce anti-Spike antibodies following two vaccine doses.…”
Section: Anti-sars-cov-2 Vaccination In Inborn Errors Of Immunitymentioning
confidence: 99%
“…This is important because otherwise, known age-related changes in the immune system would confound the results of each study. The published study designs varied from observational [71,77,[83][84][85][86][87][88][89][90][91][92][93][94][95][96] to interventional studies and clinical trials [80,82,83,97,98]. Furthermore, humoral responses were reported by seroconversion, antibody concentration/titers, and, in some cases, virus neutralization/pseudo-neutralization capacity (Figure 3 and Table 2).…”
Section: Humoral Responsementioning
confidence: 99%
“…For example, one report of individuals with STAT1-GOF (n=7) found that 57% seroconverted after two doses of vaccine [112]. Another case report on one individual with XMEN/MAGT1 deficiency reported a reactive spike-specific total antibody response after two doses of mRNA vaccine [90]. In addition, Timothy et al also completed a retrospective chart review of eight patients with CTLA-4 deficiency (two children and six adults).…”
Section: Humoral Responsementioning
confidence: 99%
“…This is important because otherwise, known age-related changes in the immune system would confound the results of each study. The published study designs varied from observational [ 74 , 80 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ] to interventional studies and clinical trials [ 83 , 85 , 86 , 101 , 102 ]. Furthermore, humoral responses were reported according to seroconversion, antibody concentration/titers, and, in some cases, virus neutralization/pseudo-neutralization capacity ( Figure 3 and Table 1 ).…”
Section: The Covid-19 Vaccination Response In Iei Patientsmentioning
confidence: 99%